2021
DOI: 10.3390/ijerph18073599
|View full text |Cite
|
Sign up to set email alerts
|

Can Microplastics Influence the Accumulation of Pb in Tissues of Blue Crab?

Abstract: The study of microplastics (MPs) and associated pollutants is essential for a better understanding of some of the factors that threaten marine ecosystems. The main objective of this study was thus to assess Pb distribution and accumulation in the tissues of blue crabs (Callinectes sapidus) exposed to MPs. Blue crabs were collected from the mouth of the river Segura (Guardamar, Spain) and fed on mussels from two Mediterranean areas with different levels of Pb contamination: Portmán Bay and San Pedro del Pinatar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…2 and 3). Munuera et al (2021) found little effect of microplastics on Pb accumulation in the muscle of the crustacean Callinectes sapidus but a high effect in the hepatopancreas. The element concentrations derived from drifted plastics, including Pb like a previous study (Munuera et al, 2021), were higher in the hepatopancreas of individuals in the more polluted site, Nita.…”
Section: Evaluation Of Trace Element Contamination In Terrestrial Her...mentioning
confidence: 78%
See 1 more Smart Citation
“…2 and 3). Munuera et al (2021) found little effect of microplastics on Pb accumulation in the muscle of the crustacean Callinectes sapidus but a high effect in the hepatopancreas. The element concentrations derived from drifted plastics, including Pb like a previous study (Munuera et al, 2021), were higher in the hepatopancreas of individuals in the more polluted site, Nita.…”
Section: Evaluation Of Trace Element Contamination In Terrestrial Her...mentioning
confidence: 78%
“…Munuera et al (2021) found little effect of microplastics on Pb accumulation in the muscle of the crustacean Callinectes sapidus but a high effect in the hepatopancreas. The element concentrations derived from drifted plastics, including Pb like a previous study (Munuera et al, 2021), were higher in the hepatopancreas of individuals in the more polluted site, Nita. Therefore, the hepatopancreas was more affected by the accumulation of trace elements via microplastics ingested from the environment than the muscles of C. purpureus, as previously found in other crustaceans.…”
Section: Evaluation Of Trace Element Contamination In Terrestrial Her...mentioning
confidence: 78%
“…The species (fish), the concentrations of MPs and Cd, and how the metal was administrated could all have led to these differences. However, in a recent study, Munuera et al [25] found no differences in the accumulation of another trace toxic element (Pb) in blue crabs exposed to the same concentrations of MPs (25 µg L −1 ). Thus, differences in the responses to the MPs could be associated with the species.…”
Section: Effects Of Microplasticsmentioning
confidence: 86%
“…), and pelagic species, usually fish [24]. The blue crab (Callinectes sapidus) is of great interest in toxicological research due to its characteristics, habits, and ease of handling, and has been used in several experimental studies [25][26][27]. This crustacean (decapod) is regarded as an invasive species along Mediterranean coasts as it originates from the Atlantic Ocean.…”
Section: Introductionmentioning
confidence: 99%
“…For example, research results showed that MPs, encapsulated within fecal pellets of the copepod Centropages typicus, could be transferred to copepod Calanus helgolandicus via coprophagy [42]. This could also increase their potential to enhance the transport of other pollutants absorbing on the MPs [37,45].…”
Section: Long-term Exposure Assaymentioning
confidence: 99%